The Use of Interactive Multimedia to Increase Students’ Motivation and Achievement in Learning Islamic Education - Sukamto; Ummah, Putri Irsya Datul; Fahruddin, Mohammad Ali (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to analyze the use of interactive multimedia to increase student motivation and achievement in learning Islamic Education. This research uses a qualitative method. The informants of this research are the Principal, Deputy Head of Curriculum, teachers, and students. The data collection techniques used in this research are in-depth interviews, observation, and documentary studies. Qualitative data analysis used are data condensation, data display, and verifications. This research uses source and method triangulation techniques to check the validity of the data. The results of this study are: (1) Teachers develop multimedia learning videos using the material and local wisdom. The video is edited with Windows Movie Maker and Kine-master applications. The videos are used in offline and online learning; (2) Interactive PowerPoint multimedia maximizes the hyperlink feature, so that it can be combined with various other sources such as: youtube, websites, images, quizzes, animations, and others; (3) A special team designs google forms. This media is also used as an evaluation, announcement, and survey. The constraints of interactive multimedia utilization are that the internet network is not smooth, not all students have personal mobile phones, lack of parental awareness, and not all teachers can develop their google forms.